A nation of veterans war, citizenship, and the welfare state in modern America - Burtin, Ulrich ca. 20. Jh (University of Pennsylvania Press, 2022)
"In examining how the veterans' movement inscribed martial citizenship onto American law, politics, and culture, A Nation of Veterans offers a new history of the U.S. welfare state that highlights its longstanding connection with warfare. It shows how a predominantly white and male group such as military veterans was at the center of social policy debates in the interwar and postwar period and how women and veterans of color were often discriminated against or denied access to their benefits. It moves beyond the traditional focus on the 1944 G.I. Bill to examine other important benefits like pensions, civil service preference, and hospitals. The book also examines multiple generations of veterans, by shedding light on how former service members from both World Wars as well as Korea and the Cold War interacted with each other"--
Includes bibliographical references and index
Keywords: Sozialhilfe; Veteran; USA; Veterans / Government policy / United States / History / 20th century; Veterans / Services for / United States / History / 20th century; Veterans / Political activity / United States / History / 20th century; Welfare state / United States / History / 20th century; Public welfare / Political aspects / United States; Veterans / United States / Societies, etc; Veterans / Legal status, laws, etc / United States; United States / Social policy / History / 20th century